Knowledge, Attitudes, and Practices of Parents on Early Childhood Caries in Qatar—A Questionnaire Study - Al-Jaber, Aisha Saleh; Al-Qatami, Hadeel Mohammad; Abed Al Jawad, Feras Hasan (European Journal of Dentistry, 2021)
Objectives The aims of the present study were to evaluate the level of knowledge, attitudes, and practices (KAP) toward early childhood caries (ECC) in a group of Qatari parents and to assess the association of sociodemographic factors on their KAP.Materials and Methods A cross-sectional study which was based on a piloted self-administered questionnaire was conveniently distributed to parents who attended the Pediatric Dentistry Section, Hamad Dental Center (HDC), Doha, Qatar. The questionnaire comprised four parts which asked about sociodemographic characteristics, knowledge, attitudes, and practices. A score for each domain was given based on the percentage of correct answers.Statistical Analysis Descriptive and analytical statistics were employed. For descriptive statistics, frequency of distribution in relation to sociodemographic characteristics and responses to items of the questionnaire were presented. For analytical statistics, associations between independent variables and KAP were employed using Chi-squared tests.Results The overall mean scores of KAP were 60.8%, 65.6% and 72.7%, respectively. Females had significantly higher percentages of correct answers than males (p = 0.001). Only 20% of females had poor knowledge, while it was 40% in males. Parents with university or higher degrees had significantly higher percentage of good attitudes than parents with preparatory or less education (p = 0.05). Areas that necessitated improvement by parents included the following: the amount of toothpaste needed for brushing, signs of tooth demineralization, bacteria that causes tooth decay can be transmitted from mother to her child, and tooth decay can be transmitted by sharing utensils (i.e., spoons, forks).Conclusions The overall KAP of parents toward ECC was relatively fair. However, certain socioeconomic factors (SEF) seemed to influence each domain, and areas of improvement are needed. Areas of improvement are needed in each domain. Mothers were significantly more knowledgeable than fathers regarding oral health issues of their children. Highly educated parents demonstrated better attitudes than the less educated. Continuous educational programs coordinated by health regulatory bodies should be introduced to improve parents' KAP regarding ECC risk factors and prevention.
Keywords: early childhood caries; knowledge; attitudes; practices; questionnaire; socioeconomic factor